137k views
3 votes
M+30/m^2 -16 / m^2 -9/m+4

User Masae
by
7.0k points

1 Answer

4 votes

Answer:

(m + 30) / [(m - 4)(m + 3)(m - 3)].

Explanation:

m+30/m^2 -16 / m^2 -9/m+4.

m+30/m^2 -16

= m + 30

----------

(m - 4)(m + 4)

m^2 -9/m+4

= (m + 3)(m - 3)

--------------------

m + 4

So m+30/m^2 -16 / m^2 -9/m+4

= (m + 30/ m^2 - 16 * m + 4 / m^2 - 9

= m + 30 m + 4

---------- * ------------

(m - 4)(m + 4) (m + 3)m - 3)

= (m + 30)

--------------------- (answer).

(m - 4)(m + 3)(m - 3)

User Macka
by
7.2k points